FAKTOR-FAKTOR YANG MEMPENGARUHI KEMANDIRIAN LANSIA DI WILAYAH PUSKESMAS SIMPANG KATIS KABUPATEN BANGKA TENGAH TAHUN 2023 - Ikasari, Linda; Sari , Indah Permata; Maryana, Maryana (Seroja Husada: Jurnal Kesehatan Masyarakat, 2024)
Physical activity is very important for the elderly, because it is a form of prevention against various degenerative diseases and can train the elderly to be independent in carrying out daily activities. This study aims to determine the factors that affect the independence of the elderly in the Simpang Katis Health Center Area, Central Bangka Regency. This research was designed using a cross-sectional research design with independent variables (pain, anxiety and family support) and a dependent variable (elderly independence) with a sample of 62 people. The results of the study used the Chi-Square Test, namely pain p-value 0.000 < 0.05, anxiety p-value 0.000 < 0.05 and family support p-value 0.000 < 0.05. This shows that there is a significant relationship between pain, anxiety and family support on the independence of the elderly in the Simpang Katis Community Health Center Area, Central Bangka Regency. The results of this research are expected to provide benefits for researchers to broaden insight and knowledge and can be used as research reference material and further refer9nce so that it can be developed in the application of nursing care.